PERBANDINGAN KEMAMPUAN BELAJAR MANDIRI MAHASISWA FK UMSU SEBELUM DAN SETELAH PANDEMI COVID - 19 - SYAFIQAH TSAMARAH AGHLA PANE; RATIH YULISTIKA UTAMI (JURNAL ILMIAH SIMANTEK, 2021)
The COVID-19 pandemic has had a major impact on various fields, one of which is education. During the COVID-19 pandemic,various problems were encountered, such as online learning which has many demands, one of which is the ability to learnindependently. To compare the independent study abilities of UMSU Medical Faculty students before and after the COVID-19pandemic. This study is a comparative analytic study with a cross-sectional approach. The independent learning ability offemale students is higher than that of male students. Students who have the ability to study independently before the pandemicare third year students. Students with 5-12 hours of free time have the ability to study independently before and after thepandemic. Then students who live alone or in boarding houses have higher independent learning abilities compared tostudents who live with their families or parents. Students with very satisfactory learning achievements have high levels ofindependent learning abilities before and after the pandemic. There is a significant difference in the independent study abilityof UMSU Medical Faculty students before and after the COVID-19 pandemic (p<0.00). Students' self-study ability after thepandemic is better than before the pandemic.